Void evolution and porosity under arsenic ion irradiation in GaAs1−xSbx alloys. (20th February 2017) - Alkhaldi, H S; Kluth, P; Kremer, F; Lysevych, M; Li, L; Ridgway, M C; Williams, J S
Abstract: We have studied the formation of porosity in crystalline GaAs0.25 Sb0.75 and GaAs0.5 Sb0.5 alloys under irradiation with 140 keV As − ions over a wide range of temperature (−180 to 400 °C) and ion fluences ranging from 1 × 10 13 to 2 × 10 17 ions cm −2 . The GaAs0.25 Sb0.75 alloy showed only little swelling (in comparison with GaSb), with void formation and sputtering both playing an important role in the materials modification. The initiation of voids and their evolution in the alloy strongly depends on the ion fluence and irradiation temperature, as well as the As content in the alloy. Porosity is largely suppressed in the GaAs0.25 Sb0.75 alloy, with the major change being void formation. For the GaAs0.5 Sb0.5 alloy, it was rendered amorphous with no apparent pores or void structures and only sputtering effects were observed at high ion fluence. In addition, the transformations from crystalline to amorphous and to a void or a porous structure occurred simultaneously in the GaAs0.25 Sb0.75 alloy. The mechanisms responsible for such changes are consistent with point defect movement and segregation.